2020
DOI: 10.1038/s41598-020-68100-4
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of the lung microbiome in intensive care patients with chronic obstructive pulmonary disease and community-acquired pneumonia

Abstract: Little is known about the composition and clinical implications of lung microbiome in patients with chronic obstructive pulmonary disease (COPD) and community-acquired pneumonia requiring invasive mechanical ventilation and intensive care unit admission. Therefore, this study aimed to explore the longitudinal changes in microbial airway composition and its variations between COPD patients with different weaning outcomes. Fifty-one endotracheal aspirate samples from 21 participants and 5 saline samples were col… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 23 publications
0
6
1
Order By: Relevance
“…About the correlation of clinical factors and microbiome α diversity and β diversity, the predisposition course of antibiotics before hospitalization was indicated to be associated with both α and β diversity. The easier choice for empirical antimicrobial drugs in front of febrile episodes in children with hematological malignancies may be the major cause to this situation, which was comprehensible and common nowadays, whereas, in this study, alanine transaminase revealed a significant correlation with α diversity, which was scarcely reported in previous studies ( 32 , 41 – 43 ). There was a great need for further study about this term.…”
Section: Discussioncontrasting
confidence: 73%
“…About the correlation of clinical factors and microbiome α diversity and β diversity, the predisposition course of antibiotics before hospitalization was indicated to be associated with both α and β diversity. The easier choice for empirical antimicrobial drugs in front of febrile episodes in children with hematological malignancies may be the major cause to this situation, which was comprehensible and common nowadays, whereas, in this study, alanine transaminase revealed a significant correlation with α diversity, which was scarcely reported in previous studies ( 32 , 41 – 43 ). There was a great need for further study about this term.…”
Section: Discussioncontrasting
confidence: 73%
“…Gut microbiota have recently been recognized as an important factor influencing the pulmonary system, hence, the term “gut–lung axis.” 86 In a prospective study of 21 chronic obstructive pulmonary disease patients who were intubated and admitted to the ICU, sequential endotracheal sampling revealed that an increase in the relative abundance of the Acinetobacter genus and Acinetobacter baumannii complex species was associated with decreased chances of successful weaning. 87 In another study, among patients admitted to the ICU and maintained on supplementary oxygen, exposure to hyperoxia independently predicted subsequent bacterial growth from lung specimens, with notable species-specific effects. Specifically, rates of Staphylococcus aureus isolation were not affected by early exposure to hyperoxia, whereas rates of Pseudomonas aeruginosa isolation decreased among patients receiving high concentrations of fractional inspired oxygen tension.…”
Section: Gut Microbiome In Intensive Carementioning
confidence: 99%
“…Some of these investigations have identified new potential markers of poor prognosis in ICU patients [9] . For example, a shift towards an Acinetobacter -dominant microbiome in patients with COPD was associated with weaning failure, suggesting that the bacterial community structure can impact weaning outcomes [17] . Additionally, Dickson et al found that gut-associated bacteria ( Pasteurellaceae spp.…”
Section: Towards a New Conceptual Framework Of Vapmentioning
confidence: 99%